Adaptive Observer Design for a Bidirectional AC/DC totem pole PFC Power Converter. Issue 12 (2022) - Bentalhik, I.; El fadil, H.; Lassioui, A.; Koundi, M.; El idrissi, Z.; Giri, F.
Abstract: In this paper, we propose a nonlinear observer for a single-phase bidirectional AC/DC totem-pole power factor correction (PFC) converter intended to be used in wireless power transfer (WPT) chargers for electric vehicles (EVs). This converter is gaining a lot of interest recently as it entails power losses reduction which is a key desirable factor in WPT chargers. Secondly after introduction, its operating principle during grid to vehicle (G2V) and vehicle to grid (V2G) power transfer modes is presented. Thirdly, an overall mathematical model governing all the operating modes of the converter is elaborated. Fourthly, a nonlinear observer-based Kalman Like technique is designed for estimating the involved state variables and also the converter's parameters. Finally, it was shown, using simulation results, that the estimated state variables match well the measured ones which verify the accuracy of the proposed observer. It is worth noting that the designed observer is a cost-effective solution since it requires only one measurement which is chosen as the grid current.